Markedly raised levels of C‐reactive protein are associated with culture‐proven sepsis or necrotising enterocolitis in extremely preterm neonates. (1st April 2015) - Keane, Michelle; Fallon, Rachel; Riordan, Andrew; Shaw, Ben
Abstract Aim A serious inflammatory process is suspected when C‐reactive protein (CRP) is very high, and we established the causes and outcomes when CRP was >100 mg/L in neonates. Methods We retrospectively reviewed all 277 episodes where CRP exceeded 100 mg/L between January 2007 and December 2011 at a tertiary neonatal unit. Results Of the 6025 neonates admitted during the study period, 258 had CRP >100 mg/L at least once. The overall mortality rate was 44/258 (17%); 36 died within 7 days of CRP >100 mg/L, and 34 were extremely preterm infants. CRP exceeded 100 mg/L in 106 infants within the first 3 days of life – 74 term, 25 preterm and seven extremely preterm – with no infection identified in 81%. In contrast, infections were found in 87% of the 171 episodes from day four of life – 129 extremely preterm, 23 preterm and 19 term – predominantly coagulase‐negative staphylococcus sepsis and necrotising enterocolitis. Conclusion Markedly elevated CRP in the first 3 days of life was most likely to affect term neonates (74/106) with no infectious cause (81%). However, CRP >100 mg/L from the fourth day of life was most likely to affect extremely preterm neonates (129/171) and have an infectious cause (87%).